The Impact of Using the Gradual (Self-Taught) Method in Teaching Some Basic Volleyball Skills to First-Year Students in the Department of Physical Education and Sports Sciences (College of Basic Education Research Journal, 2026)
The aim of this research is to identify the use of the gradual (self-taught) method in teaching the overhand serve skill (Tennis) and the skill of (passing from above) and the skill of receiving from below for first-year students in the Department of Physical Education and Sports Sciences. The researcher used the experimental method as it suited the nature of the research. The research sample consisted of (40) students, with (20) students in each section, selected by lottery. Section (A) was named the experimental group, and Section (B) was named the control group, in which the traditional, rigid teaching method was used. Then, equivalence was achieved between the two sections. The experiment was conducted in two groups over eight weeks, with one 90-minute learning session per week. The experiment began on Sunday, December 2, 2025, and concluded on Sunday, February 1, 2026. The researcher used the SPSS program to statistically analyze the data, and after analyzing the data statistically, the researcher reached the following conclusions The effectiveness of the gradual (self-directed) method in learning the skills of the overhand pass and the passing skill. There was a variation in the performance level of some skills. The gradual (self-directed) method proved superior to the traditional method in learning some volleyball skills.
Keywords: Gradual; Self-Taught; Skills